Effect of primary care-based education on reassurance in patients with acute low back pain: Systematic Review and Meta-analysis - Traeger, Adrian C.; Hübscher, Markus; Henschke, Nicholas; Moseley, G. Lorimer; Lee, Hopin; McAuley, James H. (JAMA internal medicine, 2015)
Importance Reassurance is a core aspect of daily medical practice, yet little is known on how it can be achieved. Objective To determine whether patient education in primary care increases reassurance in patients with acute or subacute low back pain (LBP). Data Sources Medline, EMBASE, Cochrane Central Register for Controlled Trials, and PsychINFO databases were searched to June 2014. Design Systematic review and meta-analysis of randomized and nonrandomized clinical trials. Study Selection To be eligible, studies needed to be controlled trials of patient education for LBP that were delivered in primary care and measured reassurance after the intervention. Eligibility criteria were applied, and studies were selected by 2 independent authors. Main Outcomes and Measures The primary outcomes were reassurance in the short and long term and health care utilization at 12 months. Data Extraction and Synthesis Data were extracted by 2 independent authors and entered into a standardized form. A random-effects meta-analysis tested the effects of patient education compared with usual care on measures of reassurance. To investigate the effect of study characteristics, we performed a preplanned subgroup analysis. Studies were stratified according to duration, content, and provider of patient education. Results We included 14 trials (n = 4872) of patient education interventions. Trials assessed reassurance with questionnaires of fear, worry, anxiety, catastrophization, and health care utilization. There is moderate- to high-quality evidence that patient education increases reassurance more than usual care/control education in the short term (standardized mean difference [SMD], −0.21; 95% CI, −0.35 to −0.06) and long term (SMD, −0.15; 95% CI, −0.27 to −0.03). Interventions delivered by physicians were significantly more reassuring than those delivered by other primary care practitioners (eg, physiotherapist or nurse). There is moderate-quality evidence that patient education reduces LBP-related primary care visits more than usual care/control education (SMD, −0.14; 95% CI, −0.28 to −0.00 at a 12-month follow-up). The number needed to treat to prevent 1 LBP-related visit to primary care was 17. Conclusions and Relevance There is moderate- to high-quality evidence that patient education in primary care can provide long-term reassurance for patients with acute or subacute LBP.
Gesehen am 06.07.2020